High hydrostatic pressure induced changes on palm stearin emulsions. (July 2018) - Sevdin, Sezen; Ozel, Baris; Yucel, Umut; Oztop, Mecit Halil; Alpas, Hami
Abstract: Emulsions are thermodynamically unstable systems formed through blending of two immiscible fluids. Recent studies have shown that High Hydrostatic Pressure (HHP) can initiate or accelerate lipid crystallization in emulsions. In this study, the effect of HHP on lipid crystallization was examined. Emulsion samples were prepared with palm stearin (PS) as the oil phase and sodium caseinate (SC) as the emulsifier and they were pressurized at 100 and 500 MPa at 10, 20 and 40 °C for 15 min. In order to determine the crystal structure of the emulsions, differential scanning calorimeter (DSC) was used and the change in the crystal morphology during 28 day-storage at 4 °C was observed. Nuclear Magnetic Resonance Relaxometry (NMR) experiments were also conducted and transverse relaxation time (T2 ) and self-diffusion coefficient (SDC) values showed a trend to follow polymorphic changes of lipid crystals. Results showed that pressure and storage time both had significant effects (p < 0.05) on the crystal structures of emulsions. Highlights: HHP is effective on crystal morphology. HHP generates more stable β lipid crystals. Transverse relaxation time increases with increasing pressure. Self diffusion coefficients decreases with increasing pressure.